The Impact of the Sports Education Athletic Season on the Learning Motivation as Supporters of the Kurikulum Merdeka - Ginanjar, Agi; Anggraeni, Reni (CV Rezki Media, 2024)
Background: Physical education learning in Indonesia has had to switch to using the Kurikulum Merdeka which focuses more on students as the center of learning with project reports and project themes. Motivation is very important for students in following the learning process. Sport Education is a learning strategy that facilitates students and teachers with projects in the learning process and can increase student learning motivation. Objectives: The aim of the research was to examine the influence of SE on learning motivation in MTs students. Methods: The research method used in this research uses an experimental research method with a one-shot case study design. Participants in this research were 48 students at one of the MTs in Indramayu Regency. The instrument in this research used a student learning motivation questionnaire. The data analysis technique uses a one-sample t test. Results: The results of this research obtained t count = 7.05 with Sig. 0.00 < 0.05, which means that there is an influence of SE on the learning motivation of MTs students. Conclusion: This research concludes that there is an influence of SE on learning motivation in Junior High Schoolstudents.